2002
DOI: 10.1659/0276-4741(2002)022[0359:ltaidi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Larch Timberline and its Development in North China

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…However, treeline studies at the regional and local scales are needed to give further support to this idea, because often few treeline sites represent some biomes which could affect the validity of this global pattern [1]. For instance, in Mediterranean or some temperate biomes, drought, in addition to low temperatures, constrains tree growth and determines the treeline elevation [3][4][5]. In addition, based on new data from New Zealand and Chile, it was found that southern temperate treelines are driven by similar thermal thresholds as are northern treelines, thus refuting the postulated taxon-specific limitation hypothesis and confirming that southern treelines are not climatically depressed [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, treeline studies at the regional and local scales are needed to give further support to this idea, because often few treeline sites represent some biomes which could affect the validity of this global pattern [1]. For instance, in Mediterranean or some temperate biomes, drought, in addition to low temperatures, constrains tree growth and determines the treeline elevation [3][4][5]. In addition, based on new data from New Zealand and Chile, it was found that southern temperate treelines are driven by similar thermal thresholds as are northern treelines, thus refuting the postulated taxon-specific limitation hypothesis and confirming that southern treelines are not climatically depressed [6].…”
Section: Introductionmentioning
confidence: 99%
“…Air and soil temperatures diminish, affecting water availability, and increasing the probability of early frosts and the impact produced by snow (Barrera et al 2000). Trees near the boundary of their ecological distribution along altitudinal gradients (such as upper treeline) are considered the most sensitive to environmental factors, yielding the strongest expected relationships between radial growth and climate (Kullman 1993;Cullen et al 2001;Liu et al 2001;Takahashi et al 2003) Altitudinal influence on tree growth can be recorded in their tree rings (Splechtna et al 2000;Buckley et al 1997;Marchand 1980;Norton 1985). Nevertheless, studies on this subject are scarce, particularly for the southern Andean forests (Aravena et al 2002;Schmelter 2000;Villalba et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, more examples revealed that the ecotone terminology and its scopes are as individual as the persons (cf. Autio and Colpaert, 2005;Camarero et al, 2006;Holtmeier, 2009;Liu et al, 2002), also as the confused boundaries mentioned previously.…”
Section: Termsto Replace "Ecotone"mentioning
confidence: 59%